2015
DOI: 10.1209/0295-5075/109/50002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of two-flavor symmetry-locking phases in ultracold fermionic mixtures

Abstract: We describe an ultracold fermionic set-up where it is possible to synthesize a superfluid phase with symmetry obtained by locking independent invariance groups of the normal state. In this phase, named two-flavors symmetry-locking phase (TFSL), non-Abelian fractional vortices with semi-integer flux and gapless non-Abelian Goldstone modes localized on them appear. Considerations on the possible experimental realization of the TFSL are also provided. [3]. The possibility to synthesize Abelian and non-Abelian ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…1 are rescaled by their values of U cf /t: in this way they all meet in the point U c = U f = U cf . In this point all the different Hamiltonians have a U (4) symmetry and the two phases TFSL and NTFSL can be mapped onto each other, signaling a transition point between the two phases, in agreement with [39].…”
Section: A Attractive Uc U Fmentioning
confidence: 55%
See 1 more Smart Citation
“…1 are rescaled by their values of U cf /t: in this way they all meet in the point U c = U f = U cf . In this point all the different Hamiltonians have a U (4) symmetry and the two phases TFSL and NTFSL can be mapped onto each other, signaling a transition point between the two phases, in agreement with [39].…”
Section: A Attractive Uc U Fmentioning
confidence: 55%
“…A step forward towards the study of symmetry-locked states was presented in [39], based on multi-component fermionic mixtures: there a proposal for the synthesis of a superfluid phase locking two non-Abelian global symmetries has been presented. This state has been denoted as a two-flavour symmetry-locked (TSFL) state.…”
Section: Introductionmentioning
confidence: 99%
“…coincides with the mean-field Hamiltonian (33). Interestingly, this comparison sheds light on the physical meaning of the parameter γ, yielding indeed:…”
Section: Comparison At Mean-field Levelmentioning
confidence: 58%
“…Summing up, we found that the relation in (35) for the mean-field parameter γ is imposed by the request of equality between the mean-field Hamiltonians in (33) and (34), a fact physically motivated, but not trivially implied, by the equivalence of the full Hamiltonians in (21) and (5).…”
Section: Comparison At Mean-field Levelmentioning
confidence: 83%
“…Fermi gases with SU(N = 2I + 1)-symmetric interactions as realized with alkaline-earth(-like) atoms such as Yb (nuclear spin I = 1/2 and I = 5/2) [47,48] or Sr (I = 9/2) [9,49] allowed first groundbreaking experiments on thus far unexplored phenomena like SU(N ) quantum magnetism in 1D [50], the contact in a bulk SU (6) Fermi gas [51,52] or effects of spin degeneracy like Pomeranchuk cooling in SU(N ) Mott insulators [45,[53][54][55][56][57]. Isotope mixtures of SU(N )-symmetric Fermi gases [48,58] characterized by a competition between interand intraisotope interactions hold promise to exhibit exotic d-wave superfluidity [59] or two-flavor superfluid symmetry-locking phases [60,61].…”
Section: Introductionmentioning
confidence: 99%